Exergoeconomic and exergoenvironmental analysis and optimisation of the three configurations of CO2 transcritical cogeneration cycle using genetic algorithm. (2016) - Hanifi, Kaveh; Javaherdeh, Kourosh; Yari, Mortaza
In this paper, exergoeconomic and exergoenvironmental analysis and optimisation are performed for three configurations of cogeneration cycles, which differ in their energy sources. The energy sources are solar, biomass and combination of solar and biomass. Three systems are solar-CO2 transcritical cogeneration system (SCTCS), biomass-CO2 transcritical cogeneration system (BCTCS) and solar-biomass-CO2 transcritical cogeneration system (SBCTCS). Hydrogen production rate optimal design (HPROD), refrigeration power optimal design (RPOD) and cost optimal design (COD) are considered for analysis and optimisation. As a result, cogeneration using biomass is the most economic effective system among the three alternative processes. In BCTCS, the cost of products decreased 9% when hydrogen production rate and refrigeration power are decreased from 1.817 l/s to 1.754 l/s and 6.425 kW to 6.103 kW, respectively. The results indicate that the total exergy destruction rate in the PROD case is higher than any other cases; however, the investment cost rate in the HPROD is higher than the two other cases.